2002
DOI: 10.1053/ejvs.2002.1614
|View full text |Cite
|
Sign up to set email alerts
|

A Multiantioxidant Supplementation Reduces Damage from Ischaemia Reperfusion in Patients after Lower Torso Ischaemia. A Randomised Trial

Abstract: multi-antioxidant supplementation was associated with a reduction in serum CK and ASAT after AAA repair. This is likely due to a reduction in oxidative stress and a decreased leucocyte sequestration and activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
1
24
0
2
Order By: Relevance
“…Histopathologic and antiinfl ammatory effects of the peptid should also be investigated. The regulator and angiogenetic effects of VEGF have been suggested in previous studies (7,10,28). We have hypothesized that it may also have an antioxidative effect on lung injury to some extent.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Histopathologic and antiinfl ammatory effects of the peptid should also be investigated. The regulator and angiogenetic effects of VEGF have been suggested in previous studies (7,10,28). We have hypothesized that it may also have an antioxidative effect on lung injury to some extent.…”
Section: Discussionmentioning
confidence: 79%
“…Widespread distribution of VEGF and its specifi c receptors in the vasculature implies an important role for VEGF in maintenance of normal vascular function and development (8). It has been demonstrated that VEGF stimulates nitric oxide release from vascular endothelial cells (9,10).…”
mentioning
confidence: 99%
“…In contrast to the results of Lassnigg et al [17] in cardiac surgery, Wijnen et al[ 25] found a decrease in serum levels of creatine kinase, aspartate aminotransferase and lipofuscine levels in individuals undergoing infrarenal AAA repair who received preoperative supplementation with multiple antioxidants (vitamins E and C, allopurinol, NAC and mannitol). In this small (n = 42) prospective randomized trial, they did not examine renal biomarkers or AKI, and the exact mechanism that led to the decrease in the oxidant stress biomarkers is unclear.…”
Section: Oxidant Mechanismmentioning
confidence: 81%
“…Winjen e col., demonstraram que a utilização de cinco antioxidantes reduziu a incidência de IRA em pacientes submetidos à correção de aneurisma de aorta abdominal 39 .…”
Section: Bloqueadores Da Resposta Inflamatóriaunclassified